Faktor-Faktor yang Mempengaruhi Proses Pengambilan Keputusan Pembelian di Restoran Bakso Boedjangan Matraman Jakarta Timur - Gary Yefta Herbeth Siagian (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
The aims of study were to identity the characteristics of consumers, to identity the process of making purchasing decision, and to analyze the factors that influence purchasing decision at Bakso Boedjangan Restaurant Matraman, East Jakarta. The method of study were survey. The method used were an quota sampling of 100 respondents. The data were analyzed of using descriptive analysis and multiple linier regression analysis. The results showed that there are four variables that have significant effects, namely the price, the service, the varian product, and quality product. Meanwhile the location variable is a variable does not have significant influence